Clinical and neuroimaging features of patients with claustrum sign - Zhao, Chunyan; Zhang, Meijiao; Zhang, Qingping; Bao, Xinhua (Frontiers in Neurology, 2025)
ObjectiveThis study aimed at summarizing the clinical and neuroimaging features of patients with claustrum sign, so as to enhance the understanding of this imaging feature and explore its clinical significance.MethodsClinical data from 20 patients with claustrum sign were collected. The clinical characteristics, neuroimaging evolution, and outcomes were analyzed.ResultsThis cohort included 14 males and 6 females and the median age of onset was 6 years old. Diagnoses included febrile infection-related epilepsy syndrome (FIRES) in 12 cases (60%), antibody-negative autoimmune encephalitis (AbNAE) in 4 (20%), myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) in 3 (15%), and Wilson’s disease (WD) in 1 (5%). Predominant neurological symptoms included seizures (85%) and impaired consciousness (70%). The claustrum sign was observed on days 1–25 (median: day 11.5) after the onset of neurologic symptoms. It presented on the first MRI between days 1 and 14 (median: day 5.5) in 8 cases (40%), while it was absent on the first MRI (days 1–7, median: day 3) in the remaining 12 cases (60%) and appeared on the repeated MRIs (days 6–25, median: day 15). On the follow-up MRIs in 19 cases, the claustrum sign resolved on days 16–132 (median: day 53) in 17 patients, except one with AbNAE and one with WD. The patients with FIRES had the worst prognosis, all developed chronic epilepsy, 75% showed poor memory and calculation, and the median Pediatric Cerebral Performance Category (PCPC) score was 3. In contrast, patients with AbNAE and MOGAD had favorable outcomes with a median PCPC score of 1, respectively.ConclusionThe claustrum sign may represent a transient neuroinflammatory lesion and serve as an imaging marker of neuroinflammation. Lesions in the claustrum can lead to dysfunction of its connected regions, which could be one of the potential mechanisms underlying the high incidence of seizures and the impaired consciousness in children with this imaging feature. Long-term outcomes are closely related to the primary disease.